The Development of Low-Cost Airlines and Tourism as a Competitiveness Complementor: Effects, Evolution and Strategies - Moreno, Luis; Ramon, Ana; Pedreño, Andrés (Journal of Tourism, Sustainability and Well-being, 2015)
This paper addresses the relationship between the development of the airline industry and tourism. On the one hand, air transport has triggered the growth of tourism throughout the world, while, on the other hand, tourism has acted as a complementary product for developing new flight routes. This process has intensified with the emergence of low-cost carriers. A profound change has been observed in companies’ strategy to adapt to the demands of this type of market. To conduct this study, a review of the existing literature related to tourism and lowcost carriers was carried out. To conclude, an analysis of the positioning and price-fixing strategies of low-cost airlines operating on some of the most important tourist routes in Europe was performed. The results indicate different level of fares among the five companies in the sample, especially between Ryanair and easyJet, but similar pricing behaviour on the routes studied.